Dari Akidah Menuju Akhlak: Analisis Semantik Kata "Iman" dalam Al-Qur'an dan Manifestasinya dalam Perilaku - Yogi Ardiansyah; Said Azren Qadraini; Ali Akbar (Jurnal Teologi Islam, 2026)
This study examines the organic relationship between the concept of creed (īmān) and morality (akhlāq) in the Qur'an through a semantic analysis approach. The aim is to dissect the lexical meaning and semantic field of the word "īmān" and its derivatives, and to trace how this concept is imperatively manifested in the domain of behavior. Using the thematic interpretation (tafsīr maudhū’ī) method combined with Toshihiko Izutsu's semantic framework, this research analyzes all occurrences of the root word a-m-n-a in the Qur'an. The results show that "īmān" from the Qur'anic perspective is not a static concept or merely passive belief. It is a dynamic value system rooted in the basic meanings of "security" and "trust," which then evolves into total commitment. Semantically, the word "iman" is always intertwined with vocabulary of action (‘amal ṣāliḥ) and morality (khuluq), forming an inseparable unity of meaning. The behavioral manifestations of faith radiate in three main realms: (1) Vertical morality towards God (such as gratitude, patience, trust); (2) Horizontal social morality (such as honesty/ṣidq, trustworthiness, justice, and benevolence/iḥsān); and (3) Morality towards oneself (such as purification of the soul/tazkiyah al-nafs). In conclusion, this research affirms that morality is the ontological realization and empirical evidence of creed. Thus, the dichotomy between creed and morality proves to have no solid foundation in the linguistic structure of the Qur'an. Faith is inherently practical, making noble behavior the obligatory path from belief that lives within the heart.   Keyword : Īmān